REALIA IN EFL CLASSROOM: PROMOTING DESCRIPTIVE WRITING PROFICIENCY OF EIGHTH-GRADERS - Sunengko Sunengko; Nur Afifi (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2021)
Advancing students' writing skill as one of the benchmarks for the quality of literacy requires practical learning innovation. One of the models offered in this study was realia in English as a foreign language class. This research was conducted to determine if realia as a learning medium was effective to improve the students' descriptive writing ability. Quantitative was the design of this research in the form of a pre-experiment. The sample of this study consists of 19 students, 9 for male students, and 10 for female students. They were class eight at SMPI Al A'roof, Loceret, Nganjuk. The study was for three weeks and conducting five meetings. Two meetings are for collecting the data on the pre-test and post-test, and three meetings are to provide treatment to the students using realia as a learning medium in a descriptive writing class. The assessment criteria carried out include content, style, and mechanics. The data analysis indicated that the students' descriptive text writing achievement improved significantly. Therefore, it could be concluded that teaching realia writing helped develop the students' descriptive writing skills.